Fine dust risk perception, perceived restorativeness, and environmental policy support among park visitors - Yoon, Jee In; Yi, Jiwon; Joo, Jinyoung (Frontiers in Psychology, 2025)
ObjectivesFine dust (PM2.5) pollution has emerged as a severe environmental and public health issue in South Korea, affecting respiratory health and reducing outdoor physical activity levels. Given these concerns, individuals increasingly seek restorative natural environments to mitigate the psychological and physical effects of poor air quality. This study examines how fine dust risk perception influences individuals' experiences in perceived restorative environments (PRE) and their intention to support environmental policies. Specifically, this study enhances the understanding of how restorative experiences in urban parks and concerns about environmental issues influence recreationists' perspectives on environmental policies.MethodsThis study was conducted at Jeju Gotjawal Provincial Park, a well-preserved forest ecosystem known for its ecological importance. A total of 408 visitors were surveyed using purposive sampling. Participants completed a structured questionnaire assessing their fine dust risk perception, perceived restorative experience in nature, and intention to support environmental policies. Data was analyzed using confirmatory factor analysis (CFA) and structural equation modeling (SEM) to test the proposed hypotheses. In addition, a bootstrap analysis was conducted to examine the mediating effects.ResultsThe findings indicate that individuals who perceive fine dust pollution as a serious issue are more likely to experience a heightened sense of psychological and physical restoration in natural settings. Furthermore, those who find natural environments more restorative tend to express stronger support for environmental policies, suggesting that their positive experiences in nature reinforce their commitment to sustainability. The study also found that perceived restorativeness plays a key role in connecting fine dust risk perception to environmental policy support, emphasizing the importance of personal experiences in shaping pro-environmental attitudes.ConclusionsThese results highlight the role of nature-based experiences in fostering both psychological well-being and environmental engagement. As air pollution continues to pose health risks, providing access to clean, green spaces can be an effective intervention for improving public health and encouraging sustainability advocacy. Policymakers and urban planners should integrate green spaces into urban planning to enhance citizens' environmental awareness and engagement. Future studies should explore longitudinal effects and cross-regional comparisons to validate these findings further.